2016
DOI: 10.1016/j.agee.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Natural tree regeneration in agricultural landscapes: The implications of intensification

Abstract: A B S T R A C TConcern about food security is prompting a push to intensify agriculture globally. However, agricultural intensification can inhibit regeneration of vegetation in natural ecosystems. This may jeopardise the persistence of trees in agricultural landscapes and the ecosystem services these treed landscapes offer. Here, we study one of the world's most altered ecosystems -temperate eucalypt woodlands -to explore patterns in natural regeneration of trees, and factors influencing regeneration occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
0
19
0
1
Order By: Relevance
“…2a). Methods for achieving these recommendations include: 1) reducing grazing pressure and fertiliser use (Fischer et al 2009;Sato et al 2016), particularly in areas with remnant vegetation or important resources such as rocks (Michael et al 2015), and 2) embracing active restoration techniques including planting (Rey Benayas, Bullock & Newton 2008) or addition of rock where previously removed (McDougall et al 2016). Agricultural intensification that reduces tree, litter and forb cover of paddocks should be minimised.…”
Section: Management Implicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…2a). Methods for achieving these recommendations include: 1) reducing grazing pressure and fertiliser use (Fischer et al 2009;Sato et al 2016), particularly in areas with remnant vegetation or important resources such as rocks (Michael et al 2015), and 2) embracing active restoration techniques including planting (Rey Benayas, Bullock & Newton 2008) or addition of rock where previously removed (McDougall et al 2016). Agricultural intensification that reduces tree, litter and forb cover of paddocks should be minimised.…”
Section: Management Implicationsmentioning
confidence: 98%
“…Promote and recruit key habitat features such as trees, leaf litter and shrubs. Reducing grazing intensity and fertiliser application increases native vegetation recruitment (Fischer et al 2009;Sato et al 2016). Active methods of vegetation restoration include planting and rock addition (Rey Benayas, Bullock & Newton 2008;McDougall et al 2016).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Predictions are shown from the full model, in which three terms were statistically significant, namely the interactions of migratory status with vegetation type, 12-month temperature and long-term temperature this study, we sought to quantify their collective effects on different functional groups of birds (corresponding to their movement status). This approach is valuable given that multiple interacting factors can underpin species declines (Caughley & Gunn, 1996;Ceballos, Ehrlich, & Dirzo, 2017;Sato et al, 2016), and understanding these interactions is important for facilitating recoveries (Crouzeilles et al, 2016;Garnett et al, 2017;Scheele, Foster, Banks, & Lindenmayer, 2017). Indeed, many Australian birds are considered to be at increased risk of extinction as a result of climate change (Nimmo et al, 2016;Urban, 2015) and habitat loss (Garnett, Szabo, & Dutson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of agriculture on temperate deserts has been extensively evaluated in the United States and Australia (Cramer & Hobbs, ; Morris, Monaco, & Sheley, ; Standish, Cramer, Hobbs, & Kobryn, ). In these regions, agriculture reduces the richness and cover of plant species (Lesschen et al, ; Plieninger, Hui, Gaertner, & Huntsinger, ; Sato et al, ) as well as the humidity, organic matter content, and availability of nitrogen, carbon, and phosphorus in soil. However, studies on the impact of human activities such as rainfed agriculture and firewood extraction in tropical deserts are scarce because only five studies were found in the ecological literature of the last 28 years (Ayoub, ; Braimoh, ; Chidumayo, ; El Tahir, Ahmed, Ardö, Gaafar, & Salih, ; Mahiri & Howorth, ).…”
Section: Introductionmentioning
confidence: 99%